Impact of a Spatial and Regional Planning Policy for Sustainable Food Agricultural Land Protection in Banten Province - Rantau, Muhammad Ibrahim (KnE Social Sciences, 2022)
The development strategy within the regulations on Spatial and Regional Planning (Bahasa Indonesia: Rencana Tata Ruang dan Wilayah - RTRW) intersects with social, cultural, and environmental conditions. One impact is the conversion of agricultural land, plantations and forestry into industrial and residential areas. In the context of Banten Province, the regional regulation on Spatial and Regional Planning (Bahasa Indonesia: Peraturan Daerah Rencana Tata Ruang dan Wilayah - Perda RTRW) is considered to have played a major role in the conversion of agricultural land on a large scale in several regions in Banten Province. This study aimed to determine the impact of spatial and regional planning policies in Banten Province on efforts to protect sustainable food agricultural land (Bahasa Indonesia: Lahan Pertanian Pangan Berkelanjutan – LP2B), which is a national priority. The impact evaluation methodology was used to compare the condition of agricultural land before and after the implementation of this regional and spatial planning regulation. This study found a lack of strong commitment to the protection of LP2B, and that the conversion of agricultural land into industrial and residential areas largely occurred in areas that were included in the regional regulation as agricultural designation areas. Keywords: policy impact, spatial and regional planning (RTRW), land conversion